2016
DOI: 10.1097/prs.0000000000001867
|View full text |Cite
|
Sign up to set email alerts
|

The Low DIEP Flap

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Actually, Eom et al reported low DIEP of which upper border was 6 cm below the umbilicus showed significantly higher venous congestion rate than conventional DIEP flap (0% vs. 30.4%, p = 0.007). 18…”
Section: Connection Between Siev and Vc-diepmentioning
confidence: 99%
“…Actually, Eom et al reported low DIEP of which upper border was 6 cm below the umbilicus showed significantly higher venous congestion rate than conventional DIEP flap (0% vs. 30.4%, p = 0.007). 18…”
Section: Connection Between Siev and Vc-diepmentioning
confidence: 99%
“…Lowering the flap could be helpful for closing the donor site. However, clinical results of low DIEP flap are not favorable; low DIEP flaps show a relatively high rate of venous congestion [17]. Although not all conditions matched perfectly in that clinical study, inclusion of only the suprapubic area could not solve the venous drainage problem.…”
Section: Plos Onementioning
confidence: 69%
“… 18 The low DIEP can be used to reconstruct moderately sized breasts if reliable perforators exist below the umbilicus, offering the advantage of a low scar close to the pubic rim and obviating the need for umbilical detachment. 19 In case of insufficient abdominal tissue, a hybrid approach may be used, combining a pre-pectoral silicone gel implant with a DIEP flap. 20 The SIEA flap allows autologous breast reconstruction without violating the rectus fascia.…”
Section: Resultsmentioning
confidence: 99%